2019
DOI: 10.2136/sssaj2018.08.0297
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Community Structure Shifts Induced by Biochar and Biochar‐Based Fertilizer Amendment to Karst Calcareous Soil

Abstract: Biochar‐based fertilizer treatments induced significant microbial community structure shifts compared with no‐biochar and biochar alone. Biochar‐based fertilizer especially at higher biochar addition rate increased soil microbial biomass and fertility. Soil microbial species were strongly correlated with soil nutrients under biochar and biochar‐based fertilizer into karst soil. Karst ecosystems are vulnerable to degradation and constitute a significant proportion of southwestern China. Here, we explore the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…Moreover, it can increase soil microbial diversity, induce microbial community structure shifts, improve tobacco‐planting soil nutrient conditions (Zhou et al., 2019), enhance soil aeration, increase water holding capacity, and cation exchange capacity (Zheng et al., 2013). Combined with proper irrigation, it promoted the absorption of nutrients by the roots, thereby improving the quality and yield of flue‐cured tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can increase soil microbial diversity, induce microbial community structure shifts, improve tobacco‐planting soil nutrient conditions (Zhou et al., 2019), enhance soil aeration, increase water holding capacity, and cation exchange capacity (Zheng et al., 2013). Combined with proper irrigation, it promoted the absorption of nutrients by the roots, thereby improving the quality and yield of flue‐cured tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that biochar-based organomineral fertilizers maintained higher labile carbon content in soil than compost and compost combined with biochar in a short-term incubation trial (Darby et al, 2016;Nguyen et al, 2017). Zhou et al (2019) observed an increase in SOM and nutrient contents in a karst region when using biochar enriched with NPK fertilizer. Similar results were reported by Wali et al (2020), whereby they noticed an increase in soil organic matter after using P enriched biochar.…”
Section: Effect On Soil Organic Carbonmentioning
confidence: 98%
“…The application of enriched biochar could also affect the soil microorganisms by altering the soil microbial community's abundance, activity, and diversity. In the study conducted by Zhou et al (2019), the addition of biochar fertilizer increased microbial biomass and bacterial biodiversity in karst calcareous soils, showing that this material had significant benefits in restoring degraded karst soils. In addition, there was an increase in the size and complexity of the microbial correlation network, which was reflected in the greater number of nodes, links, and nodules in the cladogram derived from the LEfSe analysis.…”
Section: Effects On Soil Biological Propertiesmentioning
confidence: 98%
“…As a young and active research field, given the functional complexity of biochar, it is still necessary to conduct in-depth studies of the mechanisms by which biochar affects soil. This includes those that employ molecular biological methods, such as high-throughput sequencing, to study the biochar effects on soil microbes [81]. The effects of the long-term, continuous application of biochar on soil remain to be studied.…”
Section: Discussionmentioning
confidence: 99%